ANALYSIS OF THE INFLUENCE OF FUNDING MURABAHAH, MUDHARABAH, MUSYARAKAH, AND RAHN (PAWNING) OF GOLD TOWARD NET PROFIT OF PT BANK SYARIAH MANDIRI (BSM), TBK. - Indayatul Maulidiyah; Jeni Susyanti (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
The puspose of this study was yo analyze the influence of funding murabahah, mudharabah, musyarakah, and rahn (pawning) of gold toward net profit of PT Bank Syariah Mandiri (BSM), Tbk. This research is a case study with the object of research of PT Bank Syariah Mandiri (BSM), Tbk. The accumulation data using documentation method whit collect the financial statements in 2012-2015, while the method of analysis using multiple regression analysis. The results of this research that murabahah funding positive effect and significant towards net profit, mudharabah funding positive effect and not significant towards net profit, musyarakah funding negative effect and significant towards net profit, and rahn (pawning) of gold funding positive effect and significant towards net profit.